The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3664
|View full text |Cite
|
Sign up to set email alerts
|

Ignition Characteristics of Alternative Jet Fuels under Vitiated Conditions

Abstract: Atmospheric pressure flow reactor experiments were performed to investigate the ignition characteristics of Fischer-Tropsch and hydrotreated renewable JP-8 fuels under vitiated conditions in order to compare these properties to conventional JP-8. Ignition experiments were conducted with reactor temperatures between 832 K and 917 K with standard air as well as vitiated air with 17% O 2 and NO x levels varied between 0 and 755 ppmv. Experiments were also performed with jet fuel surrogate components such as n-dod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The presence of NO x (NO and NO 2 ) in the oxidizer stream occurs in various practical devices where combustor design includes exhaust (or flue) gas recirculation (e.g., internal combustion engines and furnaces), vitiated air (e.g., gas turbine exit streams, and high-speed propulsion test rigs), and internal recirculation zones (e.g., gas turbines). Previous works by the authors [3][4][5] showed that NO x plays a significant role in promoting ignition of jet fuels and its surrogate components. Experimental and direct numerical simulation studies of Lee et al [6] have demonstrated the importance of NO on the reignition process of a vortex-perturbed counter flow flame.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of NO x (NO and NO 2 ) in the oxidizer stream occurs in various practical devices where combustor design includes exhaust (or flue) gas recirculation (e.g., internal combustion engines and furnaces), vitiated air (e.g., gas turbine exit streams, and high-speed propulsion test rigs), and internal recirculation zones (e.g., gas turbines). Previous works by the authors [3][4][5] showed that NO x plays a significant role in promoting ignition of jet fuels and its surrogate components. Experimental and direct numerical simulation studies of Lee et al [6] have demonstrated the importance of NO on the reignition process of a vortex-perturbed counter flow flame.…”
Section: Introductionmentioning
confidence: 99%